Roth Net-Assisted Endoscopic-Guided Manometry Catheter Placement - Gurala, Dhineshreddy (Cureus, 2020)
High-resolution esophageal manometry (HRM) has become the gold standard to diagnose esophageal motility disorders. Usually, this procedure is performed by introducing the catheter, which has pressure sensors, into the esophagus and proximal stomach via the nares. Repeated coiling of the catheter and inability to pass through the gastroesophageal junction (GEJ) are common challenges encountered. Endoscopy-guided placement of the catheter can overcome these difficulties. However, sometimes even with the use of endoscopy, it is difficult to advance catheter due to anatomical variants. The extreme fragility of the catheter and sensors and the high cost of this reusable device precludes the use of biopsy forceps or snare to advance the catheter. There is no literature on using accessories during endoscopy in case of difficult placement under direct visualization. We report a unique case of using Roth Net via the suction channel to advance esophageal manometry catheter into the stomach by using endoscopy.